2010
DOI: 10.1590/s0100-39842010000600012
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo de dosimetria computacional entre modelos homogêneos e um modelo voxel em mamografia: uma discussão de aplicações em testes de constância e cálculo de dose glandular em pacientes

Abstract: OBJECTIVE: To compare data regarding dosimetry and photons fluence in different breast phantoms, discussing constancy tests and dosimetry applied to mammography. MATERIALS AND METHODS: Different homogeneous breast phantoms and one anthropomorphic voxel phantom were developed for collection of data regarding total absorbed dose in the phantom, absorbed dose in the glandular tissue material-equivalent, absorbed dose and photons fluence at different depths in the phantoms. A simulated ionization chamber collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…However, a careful approach is necessary in analysis of results obtained with such materials, as they might be different from those obtained at dosimetry on an actual breast. In their studies, Cassola et al ( 28 ) have concluded that homogeneous materials should be utilized for constancy tests and are not indicated to estimate dosimetry in actual patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a careful approach is necessary in analysis of results obtained with such materials, as they might be different from those obtained at dosimetry on an actual breast. In their studies, Cassola et al ( 28 ) have concluded that homogeneous materials should be utilized for constancy tests and are not indicated to estimate dosimetry in actual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cassola et al ( 28 ) have compared dosimetry data between different breast phantoms (homogeneous breast phantom and anthropomorphic breast phantom). They recommended the Dance ( 19 , 20 ) model as the best one to evaluate dose values in median breasts with glandular tissue in the medial region.…”
Section: Discussionmentioning
confidence: 99%